Impact of metabolic control on all-cause mortality in a nationwide cohort of patients with diabetes from Colombia - Mendivil, Carlos O.; Amaya-Montoya, Mateo; Hernández-Vargas, Juliana Alexandra; Ramírez-García, Nathaly; Herrera-Parra, Lina Johana; Guatibonza-García, Valentina; Romero-Díaz, Camila; Pérez-Londoño, Agustín; Acuña-Merchán, Lizbeth (Frontiers in Endocrinology, 2023)
Objective The magnitude of the mortality benefit conferred by good integral metabolic control in diabetes in not sufficiently known, especially among Latin American patients. We prospectively studied the association between sustained control of blood glucose (HbA1c<7%), systolic blood pressure (SBP) (<130 mmHg) and LDL (LDLc, <100mg/dL) and non-HDL (non-HDLc, <130 mg/dL) cholesterol, and death from any cause among all adult patients with diagnosed diabetes in Colombia. Methods We retrospectively analyzed data from a nationwide, centralized, mandatory registry of all patients with diagnosed diabetes assisted by the Colombian health system between July 1, 2015, and June 30, 2019. We estimated the associations of sustained achievement of each goal, and of the joint triple goal (HbA1c + SBP + LDLc) with all-cause death. Associations were assessed after adjustment for sex, age, race, insurance type and BMI in multivariable logistic models. Results We studied 1 352 846 people with diabetes. Sustained SBP (OR 0.42 [0.41-0.43]), HbA1c (OR 0.25 [0.24-0.26]) and LDLc (OR 0.28 [0.27-0.29]) control had strong negative associations with death. Moreover, among the 5.4% of participants who achieved joint, sustained metabolic control, the OR for death was 0.19 (0.18-0.21). Importantly, the impact of sustained, joint metabolic control was significantly smaller for patients of black race compared to other races (OR 0.31 [0.23-0.43] versus 0.18 [0.17-0.20], p-value for interaction <0.001), mostly at the expense of a smaller impact of LDLc control. The results were similar across body-mass index categories. Conclusions Sustained and simultaneous metabolic control was associated with remarkably lower odds of death.